2018
DOI: 10.1016/j.jom.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of introducing ship‐to‐store service on sales and returns in omnichannel retailing: A data analytics study

Abstract: Omnichannel retailing features, such as ship‐to‐store (STS) service, are designed to deliver a seamless shopping experience for customers. For a retailer, introducing omnichannel capabilities requires major investments to integrate physical stores and online marketplaces, yet holds a promise of potentially enhancing revenue streams from both brick‐and‐mortar (BM) stores and online store channels. We assess the promise of ship‐to‐store capabilities by analyzing transactional data from a national jewelry retaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 72 publications
(107 reference statements)
0
67
0
1
Order By: Relevance
“…They also showed that offline store characteristics (i.e., store density, product variety, competition) moderate these benefits of BOPS on purchase behaviors. Studies from the operational perspective indicate that BOPS implementation positively influences store traffic and offline store sales (Gallino and Moreno 2014;Gao and Su 2016;Akturk et al 2018). Moreover, Jara et al (2018) suggest that accurate stock-out information, dual experiences of website and pick-up service, and pleasant interactions with employees can create long term value for BOPS customers.…”
Section: Bops Service Qualitymentioning
confidence: 99%
“…They also showed that offline store characteristics (i.e., store density, product variety, competition) moderate these benefits of BOPS on purchase behaviors. Studies from the operational perspective indicate that BOPS implementation positively influences store traffic and offline store sales (Gallino and Moreno 2014;Gao and Su 2016;Akturk et al 2018). Moreover, Jara et al (2018) suggest that accurate stock-out information, dual experiences of website and pick-up service, and pleasant interactions with employees can create long term value for BOPS customers.…”
Section: Bops Service Qualitymentioning
confidence: 99%
“…Retailers also offer the buyonline-pickup-in-the-store (BOPS) functionality allowing consumers to buy products online and pick up in stores (Gao and Su, 2017b). BOPS is also named as ship-to-store, buy-onlineship-from-store (Serkan Akturk et al, 2018). Sending mobile messages about online promotions to offline consumers, offline-to-online targeting helps to induce consumers to shop online (Luo et al, 2020).…”
Section: Omnichannel Research In Information Systemsmentioning
confidence: 99%
“…5. Research opportunities for future research 5.1 Research opportunities for information systems Current studies regarding IT in omnichannel research have suggested some potential topics (Luo et al, 2020;Serkan Akturk et al, 2018;Song et al, 2020;Zhang et al, 2019). First, it is suggested that the design and configurations of omnichannel technologies deserve further attention.…”
Section: Advertisingmentioning
confidence: 99%
See 2 more Smart Citations